1999
DOI: 10.1021/je980266+
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibrium, Coexistence Curve, and Critical Locus for Pentafluoroethane + 1,1,1-Trifluoroethane (R125/R143a)

Abstract: The vapor-liquid equilibrium for pentafluoroethane (R125) + 1,1,1-trifluoroethane (R143a) was measured by the static method in the temperature range between 273.15 K and 313.15 K. The vapor-liquid coexistence curve near the critical point was measured by observation of the meniscus disappearance. The critical temperatures and critical densities of the 0.4118 and 0.6208 mole fraction of R125 were determined from the saturation densities along the coexistence curve in the critical region. In addition, the critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Experimental data[29]: VLE prediction for R-125 (1) + R-143a (2). Experimental data[30]: VLE prediction for R-143a (1) + R-1234yf (2). Experimental data[33]: VLE prediction for CO 2 (1) + R-32 (2).…”
mentioning
confidence: 99%
“…Experimental data[29]: VLE prediction for R-125 (1) + R-143a (2). Experimental data[30]: VLE prediction for R-143a (1) + R-1234yf (2). Experimental data[33]: VLE prediction for CO 2 (1) + R-32 (2).…”
mentioning
confidence: 99%
“…Other authors measured the critical point of the mixture (50 wt % R143a + 50 wt % R125) by observation of the vanishing meniscus between the liquid and vapor phases. 26,28 Fro ¨ba et al 26 reported a critical temperature for R507 (50 wt % R143a + 50 wt % R125), the refrigerant mixture commercially available from Solvay, of 344.06 K. Kishizawa et al 28 and Higashi 27 determined slightly lower critical temperatures for the same mixture of (343.783 and 343.76) K, respectively. These data deviate less than 0.1 % in temperature from the gas-liquid critical values obtained by our acoustic method.…”
Section: Speed Of Sound Of Liquid (51 Wt % R143a + 49 Wt % R125)mentioning
confidence: 99%
“…Higashi 27 measured the critical parameters of the R143a + R125 mixture for different compositions. To represent the composition dependence of the critical parameters of the system, the author formulated a correlation of the critical locus, having his correlation given at 343.82 K for the critical locus of (51 wt % R143a + 49 wt % R125).…”
Section: Speed Of Sound Of Liquid (51 Wt % R143a + 49 Wt % R125)mentioning
confidence: 99%
“…A summary for the binary VLE regression results ( k ij (1) and k ij (2) ) is shown in Table , where column “ x i ” represents the overall AAD in composition of both x i and y i . The AAD for each variable ( T , P , x i , y i ) for all binary systems can be found in the SI (see Table S6).…”
Section: Regressionmentioning
confidence: 99%